Perancangan Aplikasi Bahasa Daerah Tontemboan Berbasis Website - Tirsa Julianti Saruan; Arnold Horalto Umboh (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
Every region in Indonesia has its regional language, which is called the mother tongue, this language is used as a medium of communication. A regional language is a traditional language in an area which has been inherited from generation to generation by the speaking community where the language is spoken. The totemboan language itself is a cultural asset in the South Minahasa region. At present the use of regional languages, especially the tontemboan regional language among the younger generation is decreasing day by day. The younger generation prefers to keep up with the latest developments rather than using the totemboan regional language. Observation results show a decrease in regional language users, those who use the Tontemboan regional language are parents aged 50 years and over, based on this, the Tontemboan regional language is threatened with extinction. The aim of this research is to develop a website-based Tontemboan regional language application to increase cultural literacy knowledge in South Minahasa district" because there is no Tontemboan regional language dictionary application. So with the application of the Tontemboan regional language it can help to increase the knowledge of the people in South Minahasa to master the Tontemboan regional language. The method used is a prototype with five stages, for system design using Unified modeling language, and testing using black box testing. The results of testing this regional language application using alpha testing or functionality testing with a feasibility percentage result of 100% with reference to the feasibility category means that this website-based Tontemboan regional language application is very feasible for the functionality aspect. Meanwhile, the results of the beta test or usability test carried out on 52 users were 94.89%, which means this system is very feasible from the aspect of system usability. so it is concluded that the Tontemboan regional language dictionary application is very good to use